Działalność kulturalna i edukacyjna na rzecz zachowania białoruskiej tożsamości narodowej na Podlasiu - Siemakowicz, Urszula (Przegląd Środkowo-Wschodni, 2023)
This article presents the contemporary cultural and educational activities of the Belarusian minority in the Podlaskie Voivodeship. The aim of this article is to characterize the contemporary features of the model of Belarusian national identity in Podlasie and to show cultural and educational activities for its preservation. I am going to present this issue based on the analysis of historical conditions that influenced the formation of the national identity of Belarusians in Podlasie, and an approximation of contemporary cultural and educational activities undertaken by representatives of the Belarusian minority in the Podlaskie Voivodship.